Effect of proteins and phosphates on the degradation and repassivation of CoCrMo alloys under tribocorrosion conditions. (1st October 2020) - Bryant, M.; Sin, J. Rituerto; Emami, N.; Neville, A.
ABSTRACT: Cobalt-chromium-molybdenum alloys are commonly used for biomedical applications such as dental implants and joint implants. Once the material is implanted into the body it is exposed to the corrosiveness of biological fluids and, in some cases, to mechanical loading that can lead to the combined action of wear and corrosion; better known as tribocorrosion. The effect of four different simulated body fluids on the tribocorrosion behaviour of a CoCrMo alloy has been investigated. The degradation of the studied CoCrMo alloys due to tribocorrosion shows a great dependence on the chemical composition of the media. Phosphate-buffered saline (PBS)-based solutions tend to show higher mass loss than the solutions prepared with distilled water. Phosphates present in PBS tend to accumulate on the surface of the alloy and change its tribological performance. In addition, proteins show a lubricating effect reducing the coefficient of friction of the system in the boundary lubrication regime.